KOMPENSASI SEBAGAI PENYEMANGAT KERJA UNTUK MENINGKATKAN KINERJA KARYAWAN - Rachmawati, Dita; PUJI HANDAYATI; ARIEF NOVIARAKHMAN ZAGLADI (Pusat Publikasi dan Penerbitan Karya Ilmiah STIE Indonesia Malang, 2024)
Compensation is a reward given by the company to employees, for their services in carrying out the duties, obligations and responsibilities assigned to them in order to achieve company goals. Providing compensation to employees has the greatest influence on employees’ thoughts about a sense of calm that generates loyalty to the company and motivates the implementation of their work. The purpose of this study is to identify compensation as a work incentive to improve employee performance. The method used is research using literature studies by examining journals and books related to the effect of compensation as an encouragement for employee performance. The results of the discussion show that the compensation given must be felt fairly by employees and the amount of compensation is not much different from what is expected by employees. If these two things can be fulfilled, the employee will be satisfied. Satisfaction will trigger employees to continue to improve their performance, so that company goals and employee needs will be achieved together.